2015
DOI: 10.1002/jbm.a.35490
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of intra‐articular ultra‐purified low endotoxin alginate administration on an experimental canine osteoarthritis model

Abstract: Intra-articular administration of UPLE-alginate in the early stage of OA slowed disease progression in canines. UPLE-alginate may have potential as a therapeutic agent for OA patients and reduce the number of patients who need to undergo total joint arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…17 The low endotoxin level allows safe clinical application of the UPAL gel by preventing immunologic reactions to the implanted material. 24,37 The UPAL gel can instantaneously gelate in situ and enhance the cellular proliferation and chondrogenic differentiation of bone marrow–derived mesenchymal stem cells, resulting in better reparative tissues in rabbit and canine osteochondral defects. 7,8,17,34 In addition, the chemokine contained in this material enhances the recruitment of bone marrow–derived mesenchymal stem cells and successfully achieves hyaline-like cartilage repair without exogenous cellular transplantation.…”
mentioning
confidence: 99%
“…17 The low endotoxin level allows safe clinical application of the UPAL gel by preventing immunologic reactions to the implanted material. 24,37 The UPAL gel can instantaneously gelate in situ and enhance the cellular proliferation and chondrogenic differentiation of bone marrow–derived mesenchymal stem cells, resulting in better reparative tissues in rabbit and canine osteochondral defects. 7,8,17,34 In addition, the chemokine contained in this material enhances the recruitment of bone marrow–derived mesenchymal stem cells and successfully achieves hyaline-like cartilage repair without exogenous cellular transplantation.…”
mentioning
confidence: 99%
“…Thus, we used UPAL ® gel to administer CCL21 to adult injury sites. Alginate acid is known to exert a cartilage differentiation effect, and UPAL ® gel has reduced endotoxin levels and is suitable for use in vivo 11,2730 . In addition, alginate has been widely used as a scaffold biomolecule in combination with drugs, peptides and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with rabbit and canine models demonstrated that the intra-articular administration of ultrapurified low endotoxin alginate inhibited the progression of osteoarthritic changes. 15,32 In the current model, the implanted UPAL gel was considered to play roles in not only enhancing cartilage repair of the defect site but also protecting against degenerative changes of the implanted graft. One can reasonably conclude that these effects of UPAL gel enhance the repair of the entire osteochondral lesion treated with OAT alone.…”
Section: Discussionmentioning
confidence: 99%